Sustainable polycarbonate adhesives for dry and aqueous conditions with thermoresponsive properties - Anjeza Beharaj; Ethan Z. McCaslin; William A. Blessing; Mark W. Grinstaff (Nature Communications, 2019)
Adhesives are ubiquitous in commodity products, however it it essential that their synthesis and degradation be sustainable without compromising their performance. Here, the authors report a library of adhesives based on environmentally benign building blocks that perform in both dry and wet environments.